Late Neogene monsoonal climate in the southeastern margin of the Tibetan Plateau revealed by leaf physiognomy evidence - Zhuo-Er Wang; Gui-Hua Chen; Rui Cao; Zhi-Hui Song; Zhao-Shuai Wang; Huai Wang; Su-Ting Ding; Jing-Yu Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Crustal-derived versus mantle-derived carbonatites - Ben-Xun Su; Shi-Ying Wang; Jing Wang; Hong-Rui Fan (Lithos, 2024)

A review of nanoscale MnOx-based materials: Catalytic and oxidative properties for pollutant degradation in multiple mediums - Zi-Chun Lu; Hai-Zhu Liu; Rui Zhang; Bin Li; Jin-Xing Zhou; Hai-Feng Su (Journal of Water Process Engineering, 2024)

Effective purification of Fe/V as spherical phosphosiderite and porous vanadium oxyhydroxide from waste vanadium-bearing slag - Zhu Suiyi; Su Ting; Lan Xin; Htet Oo Kaung; Zheng Minglin; Wang Tianzhu; Luo Wenjing; Zhou Rui; Yang Weilu; Chen Yu (Journal of Water Process Engineering, 2024)

Efficient biodegradation of poly(butylene adipate-co-terephthalate) in mild temperature by cutinases derived from a marine fungus - Fan Fei; Zhenjie Su; Rui Liu; Rongrong Gao; Chaomin Sun (Journal of Hazardous Materials, 2024)

Immune defense adaptation of Strauchbufo raddei population in heavy metal polluted area: Insights from developmental and environmental perspectives - Rui Su; Fanrui Chen; Xueying Zhang; Yuting Qin; Yingmei Zhang; Wenya Zhang (Journal of Environmental Management, 2024)

Ultrasensitive detection of contaminants in milk using a novel NMS-Ag modified water-resistant paper substrate - Rui Su; Siqi Li; Yugang Su; Zhong Wang; Ming Gao (Food Chemistry, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Enhanced detection of 4-nitrophenol in drinking water: ECL sensor utilizing velvet-like graphitic carbon nitride and molecular imprinting - Rui Xu; Yu Su; Hongfei Ji; Man Jiang; Ruizhong Zhang; Lan Ding; Yanhua Chen; Daqian Song (Food Chemistry, 2024)

Improved nitrate removal by polyvinyl alcohol/sodium alginate hydrogel beads entrapping salt-tolerant composite bioagent AHM M3 - Rui Han; Hongjing Ma; Xin Su; Jing Song; Peiwu Liu; Yinghai Wu; Ying Liu (Desalination, 2024)

Three-dimensional discrete element simulation on mechanical response and failure characteristics of composite rock under triaxial unloading condition - Sheng-Qi Yang; Yu Song; Shi-Gui Du; Rui Yong; Su-Sheng Wang; Yun-Jin Hu; Jiang Zhao (Computers and Geotechnics, 2024)

Enhanced co-production of H2 and formic acid via Ni-facilitated Cu+/Cu2+ cycling in an industry-level hybrid water splitting system - Xinyue Tao; Rui Su; Xiangjun Meng; Dongfang Xue; Chi Zhang; Zhaoyu Feng; Kaitian Zheng; Chunjian Xu (Chemical Engineering Journal, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Integrated Transcriptome Analysis of lncRNA, miRNA, and mRNA Reveals key Regulatory Modules for Polycystic Ovary Syndrome - Rui Lin; Saihua Zheng; Haiyu Su; Guiying Wang; Xuelian Li; Chenqi Lu (Phenomics, 2024)

TP53 to mediate immune escape in tumor microenvironment: an overview of the research progress - Kai-li Zhu; Fei Su; Jing-ru Yang; Ruo-wen Xiao; Rui-yue Wu; Meng-yue Cao; Xiao-ling Ling; Tao Zhang (Molecular Biology Reports, 2024)
Increasing evidence suggests that key cancer-causing driver genes continue to exert a sustained influence on the tumor microenvironment (TME), highlighting the importance of immunotherapeutic targeting of gene mutations in governing tumor progression. TP53 is a prominent tumor suppressor that encodes the p53 protein, which controls the initiation and progression of different tumor types. Wild-type p53 maintains cell homeostasis and genomic instability through complex pathways, and mutant p53 (Mut p53) promotes tumor occurrence and development by regulating the TME. To date, it has been wildly considered that TP53 is able to mediate tumor immune escape. Herein, we summarized the relationship between TP53 gene and tumors, discussed the mechanism of Mut p53 mediated tumor immune escape, and summarized the progress of applying p53 protein in immunotherapy. This study will provide a basic basis for further exploration of therapeutic strategies targeting p53 protein.

Small intestine structural and functional responses to environmental heavy metal stress in tree sparrow Passer montanus nestlings - Fei Jin; Yue Shen; Zhaocun Lin; Yuquan Miao; Yu Liu; Rui Su; Wenya Zhang; Yingmei Zhang (Environmental Science and Pollution Research, 2024)

Association between particulate matter exposure and acute ischemic stroke admissions in less-polluted areas: a time-series study using a distributed lag nonlinear model - Xiaoxiao Song; Xiaolan Huang; Jinling Li; Liming Lu; Rui Qin; Miaomiao Xu; Li Su; Lian Gu (Journal of Environmental Health Science and Engineering, 2024)

Mechanism of the KIAA1429/KLF1/PD-L1 Axis in Regulating Immune Escape in Non-small Cell Lung Cancer - Rui Geng; Mingmin Ren; Yuhui Ma; Wen Su (Cell Biochemistry and Biophysics, 2024)

Real-time lettuce-weed localization and weed severity classification based on lightweight YOLO convolutional neural networks for intelligent intra-row weed control - Rui Hu; Wen-Hao Su; Jia-Le Li; Yankun Peng (Computers and Electronics in Agriculture, 2024)

Seasonal wet–dry transition and denitrifying communities contributed to nitrous oxide emissions in the water-level fluctuating zone of the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Zixu Guo; Junxiang Cheng; Zhongbo Yu; Ligang Xu; Qinglong L. Wu; Jin Zeng (Journal of Hydrology, 2024)

Contrasting responses of gross N transformation to oxalic acid and glucose supplement in paddy soil - Xun Duan; Shaohong Deng; Yichao Rui; Hang Qiao; Chong Ma; Youming Zhang; Yajun Hu; Yirong Su; Jinshui Wu; Xiangbi Chen (Journal of Environmental Management, 2024)

A superior material with antithrombotic properties serves as a secure adsorbent for the elimination of bilirubin in vitro and in pig models - Rui Su; Wei Liu; Gang Shi; Dongling Chen; Lihua Yan; Qian Li; Haichao Ni; Meili Yu; Liang Xu (Chemical Engineering Journal, 2024)

Ionic covalent organic framework-MXene heterojunction constructed by electrostatic interaction for stable electrocatalytic hydrogen generation - Rui Wang; Haiping Zhou; Qingqing Pan; Zhongmin Su; Shilun Qiu; Qianrong Fang; Haiyan Lu (Chemical Engineering Journal, 2024)

Molecular insights and functional analysis of isocitrate dehydrogenase in two gram-negative pathogenic bacteria - Wei Xiong; Rui Su; Xueyang Han; Mengxiao Zhu; Hongyiru Tang; Shiping Huang; Peng Wang; Guoping Zhu (World Journal of Microbiology and Biotechnology, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Crustal anatectic origin of the pegmatitic carbonate rocks in the Proterozoic Highland Complex, Sri Lanka - Ben-Xun Su; Shi-Ying Wang; P. L. Dharmapriya; Jing Wang; Sanjeewa P. K. Malaviarachchi; Kui-Feng Yang; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2024)

Shifts in organic carbon protection mechanism in agricultural soils across climatic gradients - Chong Ma; Yinhang Xia; Yichao Rui; Wei Gao; Xun Duan; Hang Qiao; Xunyang He; Yajun Hu; Daoyou Huang; Jinshui Wu; Yirong Su; Georg Guggenberger; et al. (Agriculture, Ecosystems & Environment, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

Effect of metal-modified sewage sludge biochar tubule on immobilization of chromium in unsaturated soil: Groundwater table fluctuations induced by rainfall - Lin Chen; Yinger Deng; Pengjie Li; Hongkun Yang; Hu Su; Ning Wang; Rui Yang (Chemosphere, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Effect of anaerobic duration on nitrogen and phosphorus removal and carbon source utilization in integrated denitrifying phosphorus removal and partial denitrification coupled with anammox system - Yunlong Su; Xiyao Li; Jiao Wang; Rui Du; Xiaofei Xue; Yanwei Shi; Yongzhen Peng (Journal of Cleaner Production, 2024)

Assessing open-pit mining impacts on semi-arid grassland: A framework for boundary and intensity quantification - Xiaoxiao Yan; Jing Li; Yang Shao; Tianyue Ma; Rui Zhang; Yiting Su (Journal of Cleaner Production, 2024)

Computational engine for finite element digital twins of structural dynamics via motion data - Youqi Zhang; Rui Hao; Jarkko Niiranen; Yaohua Yang; Eugen Brühwiler; Di Su; Tomonori Nagayama (Engineering Structures, 2024)

Effect of Dissolved Oxygen on Poly(3-Hydroxybutyrate-co-3-Hydroxyvalerate) Solid-Phase Denitrification: Simultaneous Nitrification and Denitrification Performance and Microbial Community - Peng Zhou; Ying Liu; Xin Su; Peiwu Liu; Rui Han (Water, Air, & Soil Pollution, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Artificial humic acid produced from wet distillers grains in a microwave-assisted hydrothermal process: Physicochemical characteristics and stimulation to plant growth - Tianlong Lei; Jie Su; Luyi Chang; Rui He; Guangchun Shan; Xiaomei Jiang; Yunhui Lei; Xiaobo Guo (Chemosphere, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Insights into the photoreactivity mechanisms of micro-sized rubber particles with different structure: The crucial role of reactive oxygen species and released dissolved organic matter - Rui Ding; Zhuozhi Ouyang; Pingshu Dong; Tianyuan Su; Jingzhen Wang; Xuetao Guo (Journal of Hazardous Materials, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Incentive-based customer-oriented rebalancing strategy for one-way shared electric vehicles in sustainable urban governance - Peng Guo; Yang Yang; Yiwei Su; Zhihua Chen; Rui Miao (Journal of Cleaner Production, 2024)

Experimental and theoretical studies on the flame retarding performances of 1,3,3,3-tetrafluoro-1-propene - Rui Zhai; Xiang Li; Yuan Zhuang; Bin Ye; Zhao Yang; Xianhui Su; Binjian Nie (Fuel, 2024)

Promotional mechanism of La-Mn-Fe modification on activated coke for NH3-SCR of NOx at low temperatures - Rui Li; Tao Yue; Yang Zheng; Guoliang Li; Jiajia Gao; Yali Tong; Jiaqing Wang; Mengying Ma; Wei Su (Fuel, 2024)

Mechanistic insights into the enhanced low-temperature activity of Cu-SSZ-13 by MnOx-CeO2 modification for standard SCR reaction and fast SCR reactions - Rui Li; Tao Yue; Yang Zheng; Guoliang Li; Jiajia Gao; Wenbo Zhang; Jiaqing Wang; Mengying Ma; Wei Su (Fuel, 2024)

Benefits and costs: Understanding the influence of heavy metal pollution on environmental adaptability in Strauchbufo raddei tadpoles through an energy budget perspective - Xueying Zhang; Rui Su; Yuting Qin; Yue Shen; Lun Jia; Wenya Zhang (Environmental Pollution, 2024)

Photochromic ionogel with a wide temperature range and fatigue resistance for high-resolution rewritable information record - Jingyue Zhang; Mengru Guo; Yuanteng Su; Wenxia Wu; Shicheng Wang; Rui Yang; Chao Xu; Hongzong Yin; Jiaheng Xu; Xiaolin Wang (Chemical Engineering Journal, 2024)

Castor Bean Meal Fertilizer Improves Peanut Yield and Quality by Regulating the Soil Physicochemical Environment and Soil Enzyme Activities - Mingjing Li; Rui Luo; Mingda Yin; Zhiyan Wang; Zhimin Su; Xiaohui Gu; Xuemei Hu; Chi Zhang; Fenglan Huang (Journal of Soil Science and Plant Nutrition, 2024)
Purpose Fertilization is important for improving crop yield and soil quality. Elucidation of the effects of castor bean meal (CBM) fertilizer on peanut yield and quality and soil fertility can lead to additional fertilization options for peanut and provide a theoretical reference for achieving a high-quality, high-yielding peanut. Methods During 2022–2023, a two-year long-term field experiment was conducted in Tongliao city, Inner Mongolia, China. No fertilizer (CK) was used as the control, and the effects of different treatments, i.e., CBM fertilizer (B1: 2520 kg ha -1 , B2: 5040 kg ha -1 , and B3: 10,080 kg ha -1 ), chemical fertilizer alone (F1: 175 kg ha -1 , F2: 350 kg ha -1 , and F3: 700 kg ha -1 ), and cow manure alone (N1: 3724 kg ha -1 , N2: 7448 kg ha -1 , and N3: 14,896 kg ha -1 ) on peanut yield and quality and soil fertility were investigated. Results The results showed that CBM fertilizer application improved soil ecology. Compared with other fertilization treatments, the soil pH of B3 treatment decreased by 8.5%, but significantly increased the contents of organic carbon (SOC), total nitrogen (TN), total phosphorus (TP), total potassium (TK), alkali-hydrolyzed nitrogen (AN), basic phosphorus (AP) and rapidly available potassium (AK) in the soil, which increased by 86.4%, 64.6%, 70.5%, 11.3%, 75.8%, 150.1%, and 116.2%, respectively, compared with CK. Meanwhile, B1, B2, N1 and N2 treatments also led to the elevation of the above indexes. In addition, the activities of urease (URE), sucrase (SUC), phosphatase (PPL), catalase (CAT), amylase (AMY) and protease (PRO) in the B3 treatment were significantly greater than those in the other fertilization treatments, with increases of 256.4%, 248.4%, 68.2%, 96.8%, 267.3%, and 155.7%, respectively, compared with CK. The B3 treatment also significantly increased the rootlet length(PRL), number of branches(BN), plant height(PLH) and lateral branch length(LBL) of the peanut plants. Compared with the other treatments, the B3 treatment had a greater peanut yields, reaching 8059.5 kg ha -1 and 9935.7 kg ha -1 in 2022 and 2023, respectively. Compared with the other treatments, the B1 treatment significantly increased the contents of protein (Pro), fat (FAT), unsaturated fatty acid (UFA) and vitamin E (VE), which increased by 23.3%, 6.1%, 1.0%, 29.1%, respectively, compared with CK, but the total sugar (TS) content was reduced by 9.1%. Correlation analysis further confirmed that peanut yield and quality were significantly correlated with soil nutrients and enzyme activities. Conclusions This study showed that the application of CBM fertilizer has certain positive effects. For example, the B3 treatment has certain potential for increasing peanut yield, and the B1 treatment can be used for peanut quality improvement. Therefore, CBM fertilizer is recommended as a new type of organic fertilizer for improving the peanut quality and yield.

Effect of surcharge width on evolution of soil arching for active and passive trapdoor - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin (European Journal of Environmental and Civil Engineering, 2024)

Late Pliocene Bauhinia s.l. (Cercidoideae, Fabaceae) fossils from Tengchong, Yunnan, southwestern China - Rui Cao; Zhi-hui Song; Zhuo-er Wang; Zhao-shuai Wang; Han-shi Li; Jing-Yu Wu; Su-Ting Ding (Review of Palaeobotany and Palynology, 2024)

June insolation gradient and ice sheet forcing on Qaidam precipitation during the middle Piacenzian warm period - Zeng Luo; Hansheng Wang; Richard V. Heermance; Junsheng Nie; Jing Yang; Xiaoli Yu; Zhao Wang; Rui Zhang; Qingda Su (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The shift in the spatiotemporal relationship between supply and demand of ecosystem services and its drivers in China - Rui Su; Cuncun Duan; Bin Chen (Journal of Environmental Management, 2024)

Particle size shapes prokaryotic communities and vertical connectivity in the water columns of the slope and central basin of the South China Sea - Zhonglin Ma; Paraskevi Mara; Lei Su; Long Wang; Huifang Li; Rui Zhang; Virginia P. Edgcomb; Jiangtao Li (Global and Planetary Change, 2024)

Metal exposure and blood lipid biomarkers in early pregnancy: A cross-sectional study - Rui Yang; Fengjiang Sun; Xiong-Fei Pan; Yingqian Su; Ping Wu; Jiaying Yuan; Yuwei Lai; An Pan; Wei Huang (Environmental Pollution, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Adaptation of freshwater partial Denitrification/Anammox (PD/A) granules to low-salt conditions: Process performance and metabolic insights - Qingliang Su; Jiawei Zhang; Ming Zeng; Rui Du; Xiaoyan Fan; Shenbin Cao (Chemical Engineering Journal, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

Association Between Multiple Metal(loid)s Exposure and Blood Lipid Levels: Evidence from a Cross-Sectional Study of Southeastern China - Guihua Du; Xiaoguang Song; Fankun Zhou; Lu Ouyang; Qi Li; Shiying Ruan; Rui Su; Shaoqi Rao; Yanhui Zhu; Jie Xie; Chang Feng; Guangqin Fan (Biological Trace Element Research, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Effects of different cold chain logistics modes on the quality and bacterial community succession of fresh pork - Su Wang; Dequan Zhang; Qingfeng Yang; Xiangyuan Wen; Xin Li; Tongjing Yan; Rui Zhang; Wei Wang; Kumayl Hassan Akhtar; Caiyan Huang; Chengli Hou (Meat Science, 2024)

Dynamic analysis of unsaturated porous media under moving loads by the time domain FEM using moving coordinates - Yanfei Pei; Qian Su; Rui Su; Kaiwen Liu; David P. Connolly; Tengfei Wang (Computers and Geotechnics, 2024)

Optimizing Blasting Schemes: A Comprehensive Approach through Macro–Micro Simulation and Field Experiment - Yun-Juan Chen; Jia-Rui Su; Hao-Shuang Wang; Hou-Lei Xi; Dong Gao (Geotechnical and Geological Engineering, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

YOLOv5-T: A precise real-time detection method for maize tassels based on UAV low altitude remote sensing images - Rui Gao; Yishu Jin; Xin Tian; Zheng Ma; Siqi Liu; Zhongbin Su (Computers and Electronics in Agriculture, 2024)

Development of a novel dual-enzyme modification method for the functionality improvement of egg yolk powder - Huan Rui; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

Fossil woods of Cryptocarya (Lauraceae) from the middle Miocene of Southwest China - Rui Zhang; Lu-Liang Huang; Shu-Feng Li; Tao Su; Alexei A. Oskolski (Review of Palaeobotany and Palynology, 2024)

Anthropogenic cycles of praseodymium in China: 2000–2020 - Shijiang Xiao; Yong Geng; Xue Rui; Ziyan Gao; Chang Su; Tianli Yao; Chen Zhong (Resources Policy, 2024)

A novel stress concentration inspection method for marine oil and gas pipeline based on UNSM - Jiaxing Xin; Jinzhong Chen; Renyang He; Rui Li; Xiaolong Li; Chang Liu; Run-kun Lu; Zhengda Su; Wenbo Han (Ocean Engineering, 2024)

Advances in photo-mediated advanced oxidation of periodate toward organics degradation - Tiehong Song; Yanjiao Gao; Xiaodan Yu; Rui Su; Qiyuan Deng; Zhe Wang (Journal of Water Process Engineering, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Tradeoffs between pH, dissolved organic carbon, and mineral ions regulate cadmium uptake by Solanum hyperaccumulators in calcareous soil - Rui Wang; Zhihao Xu; Shuai Chen; Jieqiong Su; Yu Huang; Yahu Hu (Environmental Research, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

Elastoplastic constitutive model of gravelly soil and its validation through numerical analysis of the Kobe Port Island liquefaction - Xingliang Wang; Bin Xu; Hui Su; Rui Pang (Computers and Geotechnics, 2024)

Pseudomonas aeruginosa regulator PvrA binds simultaneously to multiple pseudo-palindromic sites for efficient transcription activation - Yibo Zhu; Bingnan Luo; Xingyu Mou; Yingjie Song; Yonghong Zhou; Yongbo Luo; Bo Sun; Youfu Luo; Hong Tang; Zhaoming Su; Rui Bao (Science China Life Sciences, 2024)

Spatial heterogeneity of sedimentary organic matter sources in the Yangtze River estuary: Implications from fatty acid biomarkers - Yunhui Wang; Ni Su; Ergang Lian; Rui Wang (Marine Pollution Bulletin, 2024)

Generation of tau dephosphorylation-targeting chimeras for the treatment of Alzheimer’s disease and related tauopathies - Jingfen Su; Yue Xiao; Linyu Wei; Huiyang Lei; Fei Sun; Weixia Wang; Jun Yin; Rui Xiong; Shihong Li; Pei Zhang; Ying Zhou; Xiaochuan Wang; et al. (Science Bulletin, 2024)

Ecological restoration effectiveness assessment based on social media analytics: A case study of Yongding River, China - Kun Yu; Cuncun Duan; Bin Chen; Dan Song; Rui Su; Xuan Yang (Journal of Cleaner Production, 2024)

Highly sensitive fluoroprobe for detecting Sudan dyes in paprika utilizing carbon dot-embedded zeolitic imidazolate framework-8 - Yanjie Wang; Xiaofeng Wei; Yu Su; Rui Xu; Daqian Song; Lan Ding; Yanhua Chen (Food Chemistry, 2024)

Contrasting processes of microbial anabolism and necromass formation between upland and paddy soils across regional scales - Xun Duan; Anna Gunina; Yichao Rui; Yinhang Xia; Yajun Hu; Chong Ma; Hang Qiao; Youming Zhang; Jinshui Wu; Yirong Su; Xiangbi Chen (CATENA, 2024)

TRIM5 as a promising diagnostic biomarker of hepatocellular carcinoma: integrated analysis and experimental validation - Huanxiang Liu; Yuhong Tang; Jiahao Zhang; Gefeng Wu; Qing Peng; Chen Chen; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Guoqing Jiang; Qian Wang; et al. (Functional & Integrative Genomics, 2024)

Transcriptomic analysis of hydrogen peroxide-induced liver dysfunction in Cyprinus carpio: Insights into protein synthesis and metabolism - Wenrong Feng; Yuanfeng Xu; Shengyan Su; Fan Yu; Jianlin Li; Rui Jia; Changyou Song; Hongxia Li; Pao Xu; Yongkai Tang (Science of The Total Environment, 2024)

Comparison of organic and synthetic amendments for poplar phytomanagement in copper and lead-contaminated calcareous soil - Jieqiong Su; Qiaohong Zeng; Shuqi Li; Rui Wang; Yahu Hu (Journal of Environmental Management, 2024)

Occurrence, transmission and risks assessment of pathogens in aquatic environments accessible to humans - Yiyi Su; Rui Gao; Fang Huang; Bin Liang; Jianhua Guo; Lu Fan; Aijie Wang; Shu-Hong Gao (Journal of Environmental Management, 2024)

Ecological flow considering hydrological season and habitat suitability for a variety of fish - Xinyu Li; Qirui Zhang; Yanfang Diao; Yuzhi Shi; Shuxian Li; Chuanhui Yao; Rui Su; Shichao Guo (Ecological Modelling, 2024)

Recovery hydrotalcite from neutralization sludge of acid mine drainage with high manganese for degradation of norfloxacin with activated peroxymonosulfate - Qingsheng Xu; Zhengbo Yue; Rui Deng; Kang Su; Xin Chuai; Kai Zhang; Jin Wang (Chemical Engineering Journal, 2024)

PHLDA1 is a P53 target gene involved in P53-mediated cell apoptosis - Xuhong Song; Lulu Zhou; Wenrui Yang; Xinyan Li; Jiazi Ma; Kun Qi; Rui Liang; Meijing Li; Lingzhu Xie; Tin Su; Dongyang Huang; Bin Liang (Molecular and Cellular Biochemistry, 2024)

Rough knowledge enhanced dueling deep Q-network for household integrated demand response optimization - Yongxin Su; Tao Zhang; Mengyao Xu; Mao Tan; Yuzhou Zhang; Rui Wang; Ling Wang (Sustainable Cities and Society, 2024)

Seismic performance of LNG tanks in deep soil site considering soil-foundation-structure interaction - Zaixian Li; Su Chen; Rui Zhang; Xiang Liu; Xiaojun Li (Soil Dynamics and Earthquake Engineering, 2024)

Insight into the transformation of 4-hydroxy-3-aminophenylarsonic acid (HAPA) and its mechanisms under simulated sunlight irradiation - Yixin Zhang; Yingjie Yan; Wenjing Bai; Rui Tang; Kuizu Su; Zhen-Hu Hu (Journal of Hazardous Materials, 2024)

Soy protein isolate amyloid fibril-coated ZrO2 nanoparticles anchored in the polyurethane sponge for rapid and effective fluoride adsorption in the wide pH range - Wenjing Lu; Chunhui Zhang; Zhiwei Lin; Peidong Su; Zhaowei Qin; Xuezhi Li; Rui Wang; Yunchang Liu; Peiyao Luo; Kepeng Qiu (Journal of Environmental Chemical Engineering, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Correction to: Type I methanotrophs dominated methane oxidation and assimilation in rice paddy fields by the consequence of niche differentiation - Shengmeng Zheng; Shaohong Deng; Chong Ma; Yinhang Xia; Hang Qiao; Jun Zhao; Wei Gao; Qiang Tu; Youming Zhang; Yichao Rui; Jinshui Wu; Yirong Su; et al. (Biology and Fertility of Soils, 2024)

Type I methanotrophs dominated methane oxidation and assimilation in rice paddy fields by the consequence of niche differentiation - Shengmeng Zheng; Shaohong Deng; Chong Ma; Yinhang Xia; Hang Qiao; Jun Zhao; Wei Gao; Qiang Tu; Youming Zhang; Yichao Rui; Jinshui Wu; Yirong Su; et al. (Biology and Fertility of Soils, 2024)

Research on the estimation and spatial pattern of net tourism carbon emissions in the Yellow River Basin from 2009 to 2019 - Ruijuan Peng; Rui Su; Wanqianrong Gao; Xinhong Zhang (Environmental Science and Pollution Research, 2024)
Based on panel data and remote sensing data of cities in the Yellow River Basin in China from 2009 to 2019, and using the tourism carbon footprint and tourism carbon carrying capacity models, the tourism carbon emissions, tourism carbon carrying capacity, and net tourism carbon of 65 cities in the Yellow River Basin were calculated. The balance and dynamic changes in carbon emissions and carbon fixation of urban tourism in the past ten years were compared. The results show that (1) tourism carbon emissions in the Yellow River Basin are generally on the rise, along with a distribution characteristic of downstream > middle reaches > upstream with obvious characteristics of urban agglomeration centrality within the basin; (2) the carbon carrying capacity of tourism is higher than that of tourism. The growth of carbon emissions is relatively slow, showing a spatial distribution pattern of high in the west and low in the east, which is mainly related to the geographical environment and economic development of the city; (3) the tourism carbon emissions and tourism carbon carrying capacity in the upstream areas can basically maintain a balance, but in the middle and lower reaches of the region, they show a carbon surplus. There is a significant positive spatial correlation in urban net tourism carbon emissions, and the clusters are mainly H-H and L-L.

Effect of inorganic anions on hydrothermal removal of impurities Fe/Al from Cu-bearing polymetallic leachate - Ting Su; Fanrong Kong; Yu Chen; Jiancong Liu; Rui Bian; Suiyi Zhu (Environmental Science and Pollution Research, 2024)

Characterization of carbonaceous particles by single particle aerosol mass spectrometer in the urban area of Chengdu, China - Junke Zhang; Rui Wang; Chunying Chen; Yunfei Su; Luyao Chen; Wei Zhang; Yingwei Xi; Yangchun Yu; Ruiyan Pu; Minghui Lu; Ruohan Wu; Xuhui Shen (Environmental Science and Pollution Research, 2024)

Higher microbial C use efficiency in paddy than in adjacent upland soils: evidence from continental scale - Xun Duan; Yichao Rui; Yinhang Xia; Yajun Hu; Chong Ma; Hang Qiao; Guanjun Zeng; Yirong Su; Jinshui Wu; Xiangbi Chen (Soil and Tillage Research, 2024)

A portable on-demand therapeutic nitric oxide generation apparatus: New strategy for diabetic foot ulcers - Huihui Bian; Junjie Wang; Xiaodong Shan; Xiuqing Li; Yongjin Wang; Rui Sun; Chongxian Wang; Juan Lv; Chunlei Xing; Chunlei Hui; Dinglei Zhang; Chenxi Zhang; et al. (Chemical Engineering Journal, 2024)

Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2024)